Altered overnight levels of pro-inflammatory cytokines in men and women with posttraumatic stress disorder. (April 2019) - Küffer, Andreas; Straus, Laura D.; Prather, Aric A.; Inslicht, Sabra S.; Richards, Anne; Shigenaga, Judy K.; Madden, Erin; Metzler, Thomas J.; Neylan, Thomas C.; O'Donovan, Aoife
Highlights: We investigated overnight interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in men and women with and without PTSD. No significant differences were observed between groups at any single timepoint. Groups differed with respect to trajectories of cytokine levels. PTSD-positive participants showed more variation in IL-6 overnight. Men with PTSD showed peak TNF-α at the end of the sleep cycle, whereas male controls showed an inverted U-shaped profile. Abstract: Background: Posttraumatic stress disorder (PTSD) is associated with disturbed sleep and elevated levels of pro-inflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Studies in animals and healthy humans have also shown that disrupted sleep elevates pro-inflammatory cytokines, including IL-6 and TNF-α. A better understanding of overnight cytokine levels and sleep might shed light on possible mechanisms for elevated inflammation in PTSD. Thus, we investigated overnight levels of IL-6 and TNF-α in individuals with and without PTSD while recording sleep polysomnography (PSG). Method: Serum samples were collected from otherwise healthy, medication-free participants with chronic PTSD ( n  = 44; 50% female; M age = 30.34 ± 8.11) and matched controls ( n  = 49; 53% female; M age = 30.53 ± 6.57) during laboratory PSG. Levels of IL-6 and TNF-α were measured at hours 0, 2, 4, 6, and 8 after typical sleep onset time using serial serum samples. Plasma IL-6 and TNF-α levels were quantified using enzyme-linked immunosorbent assays. Results: Growth model analysis indicated a significant group by time interaction for IL-6 ( t [247] = -2.92, p = .005) and a significant group by sex by time interaction for TNF-α ( t [275] = 2.02, p = .04). PTSD positive men and women initially had higher IL-6 and TNF-α at sleep onset, but not at the end of their sleep cycle. Men with PTSD showed a peak of TNF-α at the end of the sleep cycle, whereas male control subjects demonstrated an inverted U-shaped profile. There were no significant differences in TNF-α levels overnight between women with and without PTSD. Conclusion: To our knowledge, this is the largest study to examine IL-6 overnight in a PTSD sample and the first study to examine overnight TNF-α in PTSD. Overnight IL-6 and TNF-α levels may be altered in individuals with PTSD compared to those without PTSD, and TNF-α trajectories also differed by sex. The current findings highlight the need to consider sex, sleep, time of day, and circadian variation when examining inflammation in PTSD. Additional research in broader study samples will be necessary to clarify associations between disrupted sleep, cytokines, and increased risk for disease in PTSD.